E-commerce industry competition in the settlement of digital business law in the metaverse era - Nilam sari, Meci (Gayaku Publisher, 2023)
This study aims to determine the development of the E-commerce Industry in the metaverse era, as well as how sellers and consumers can overcome applicable business laws without having to fight and bankrupt the economy in today's digital era. In this study, the literature study method was used as well as the findings that the researchers saw from several existing cases both in social media and in business life in the existing business environment. That we know that the more sophisticated an era is, the greater the business opportunity will be to move forward in the future so that consumers and sellers must be careful in making transactions, or obtaining certain data in doing business so that existing business laws are able to be obeyed.